Analysis of the bank’s expense management impact on profitability and liquidity indicators - Khaleel, Ameer Ali (Eximia, 2025)
The purpose of the research was to show that controlling costs is critical for banks and that this has a direct impact on profitability and liquidity. The Gulf Commercial Bank was examined from 2004 to 2023 using the use of the bank’s burden ratio to see how well the bank managed its costs. After examining each indicator, the research variables were compared using the Tail-Sen slope to show that there were significant differences. Although there were no notable changes in the employment ratio indicator, the study did discover that the burden ratio had a pronouncedly negative impact on the cash balance ratio, and positive for return on assets, and return on shareholders’ equity.